Efficacy of pazopanib with or without gemcitabine in patients with anthracycline- and/or ifosfamide-refractory soft tissue sarcoma: final results of the PAPAGEMO phase 2 randomized clinical trial - Schmoll, Hans-Joachim; Lindner, Lars H.; Reichardt, Peter; Heißner, Klaus; Kopp, Hans-Georg; Kessler, Torsten; Mayer-Steinacker, Regine; Rüssel, Jörn; Egerer, Gerlinde; Crysandt, Martina; Kasper, Bernd; Niederwieser, Dietger; et al. (JAMA oncology, 2021)
Pazopanib and gemcitabine have shown good tolerability, albeit modest single-agent activity in pretreated soft tissue sarcoma. A combined regimen to improve outcomes is required.To determine the efficacy of gemcitabine and pazopanib compared with pazopanib alone.This multicenter, randomized phase 2 clinical trial was conducted in Germany from September 2011 to July 2014 and included patients with an Eastern Cooperative Oncology Group performance status score of 0 to 2, adequate organ function, measurable lesion, and progression after at least 1 prior treatment with anthracyclines and/or ifosfamide. Data analysis was performed during 2019 and 2020.Patients were randomized to pazopanib with gemcitabine (A) or without gemcitabine (B).The primary end point was progression-free survival rate (PFSR) at 12 weeks; secondary end points included toxicity, quality of life, overall survival, and response rates.A total of 90 patients were randomized, and 86 eligible patients (43 women [50%]) were evaluable, with a median age of 57 (range, 22-84) years and Eastern Cooperative Oncology Group performance status score of 0/1 in 77 participants (90%). The predominant histological subtypes were leiomyosarcoma (22 [26%]) and liposarcoma (16 [19%]). After a median follow-up of 12.4 (range, 1-48) months, the primary end point was met, with a PFSR at 12 weeks of 74% (A) vs 47% (B) (hazard ratio [HR], 1.60; 90% CI, 1.15-2.23; P = .01). In the combination arm, PFSR was significantly longer, with a median of 5.6 vs 2.0 months (HR, 0.58; 95% CI, 0.36-0.92; P = .02) compared with single-agent pazopanib, whereas overall survival was similar, with 13.1 vs 11.2 months (HR, 0.98; 95% CI, 0.60-1.58; P = .83). The objective response rate was overall low, with 11% (A) vs 5% (B) (P = .10). The toxicity of the combination of pazopanib and gemcitabine was increased, but it was manageable and mainly hematological.This phase 2 randomized clinical trial of patients with soft tissue sarcoma found that the addition of gemcitabine to pazopanib was tolerable, and PFSR at 12 weeks was significantly higher compared with pazopanib alone. These results suggest clinical activity of the combination, but they should be confirmed in a phase 3 trial in a more homogeneous population (eg, leiomyosarcoma).German Clinical Trials Identifier: DRKS00003139